If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(-5n+2)=-5n-37
We move all terms to the left:
4(-5n+2)-(-5n-37)=0
We multiply parentheses
-20n-(-5n-37)+8=0
We get rid of parentheses
-20n+5n+37+8=0
We add all the numbers together, and all the variables
-15n+45=0
We move all terms containing n to the left, all other terms to the right
-15n=-45
n=-45/-15
n=+3
| 4=30+2x | | -2(2x-1)=-4x+2 | | −5c2+c−18= −6c2−6c2 | | Y=x+2/3 | | -3/5x-2=10 | | -5(k-8)=-2(8k+2) | | 4×v×6=30 | | N-4+2n=-4 | | 112n^2-567=0 | | 28=-7/3v | | −5=n/2 | | 10=x+4/8 | | −8x2−3x−8=0−8x2−3x−8=0 | | 10(v+2)-4v=2(3v+1)-3 | | 6x+7500=51900 | | 4x+4=-64 | | n/15=10-4 | | −5=n2 | | 10a+9=-9 | | 2x-4+8=9x+4x-84 | | 2=n|2+6 | | 6/11x-7=-25 | | 38+3r=10r | | 5x+30=1540 | | 11=4x-23 | | -3+2x=-12-3x | | 6(n=5)=2 | | 3x-2300=42700 | | 3x-5+91=203 | | 3b-2+7b-12-2b+14=0 | | -2(x+3)=-2(x+1) | | -11+1+6x+6=1+5x |